The effect of oxygenate fuels on PN emissions from a highly boosted GDI engine. (1st August 2018) - Leach, Felix C.P.; Stone, Richard; Richardson, David; Turner, James W.G.; Lewis, Andrew; Akehurst, Sam; Remmert, Sarah; Campbell, Steven; Cracknell, Roger
Abstract: Gasoline Direct Injection (GDI) engines are increasingly available in the market. Such engines are known to emit more Particulate Matter (PM) than their port-fuel injected predecessors. There is also a widespread use of oxygenate fuels in the market, up to blends of E85, and their impact on PN emissions is widely studied. However the impact of oxygenate fuels on PN emissions from downsized, and hence highly-boosted engines is not known. In this work, PN emissions from a highly boosted engine capable of running at up to 35 bar Brake Mean Effective Pressure (BMEP) have been measured from a baseline gasoline and three different oxygenate fuels (E20, E85, and GEM – a blend of gasoline, ethanol, and methanol) using a DMS500. The engine has been run at four different operating points, and a number of engine parameters relevant to highly-boosted engines (such as EGR, exhaust back pressure, and lambda) have been tested – the PN emissions and size distributions have been measured from all of these. The results show that the oxygenate content of the fuel has a very large impact on its PN emissions, with E85 giving low levels of PN emissions across the operating range, and GEM giving very low and extremely high levels of PN emissions depending on operating point. These results have been analysed and related back to key fuel properties.